The Incidence and Persistence of Cyclical Job Loss in New Zealand - David C. Maré; Richard Fabling (Institute for the Study of Labor (IZA), 2013)
In New Zealand, the impact of the Global Financial Crisis (GFC) was milder than in most other developed countries, with employment declining by 2.5 percent between 2008q4 and 2009q4. Job and worker turnover rates both declined, signalling a reduction in labour market liquidity and difficulties for new entrants and high-turnover groups of workers (Fabling and Maré, 2012). The current paper documents the extent and composition of employment change between 2000 and 2011, focusing on the 2008-2010 period, when the labour market impacts of the GFC were strongest. As in previous downturns, the incidence of cyclical job loss and unemployment fell disproportionately on young and unskilled workers. The paper identifies, by age, gender and earnings level, the sensitivity of employment growth and labour market flows to aggregate employment fluctuations and also to relative fluctuations across industries and regions. The accession rate is particularly sensitive to the economic cycle, most strongly for young workers. Differences in the size of cyclical employment fluctuations reflect differing responsiveness to common shocks and not exposure to different industry and local shocks. Finally, the paper traces outcomes for workers whose jobs end, summarising their duration out of work and the wage increases or reductions they experience when they secure employment. Workers who left or lost jobs spent longer out of work after the GFC and settled for lower earnings growth when they did find a job. Both of these effects had partly but not fully abated within 3 years of the onset of the GFC.
Keywords: E24; E32; J21; 330; Global Financial Crisis; cyclical job loss; unemployment; earnings growth